2011
DOI: 10.1016/j.ejcts.2010.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of visceral pleural, lymphovascular and perineural invasion in completely resected non-small cell lung cancer

Abstract: The presence of visceral pleural or lymphovascular invasion can show higher risk of mortality whereas perineural invasion has no effect on prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
3
32
1
Order By: Relevance
“…Previous studies had reported that a number of pathological factors are associated with survival rate, including visceral pleural invasion (33), vascular invasion (34) and perineural invasion (35). In the present study, it was identified that bronchial involvement was an independent predictor of OS and DFS rates, however, the status of pulmonary vascular wall invasion, visceral pleural invasion, lymphovascular invasion and perineural invasion demonstrated no significant association with survival rate.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies had reported that a number of pathological factors are associated with survival rate, including visceral pleural invasion (33), vascular invasion (34) and perineural invasion (35). In the present study, it was identified that bronchial involvement was an independent predictor of OS and DFS rates, however, the status of pulmonary vascular wall invasion, visceral pleural invasion, lymphovascular invasion and perineural invasion demonstrated no significant association with survival rate.…”
Section: Discussioncontrasting
confidence: 52%
“…In literature reports, the reported incidence of perineural invasion was 3-29%. [24][25][26] In our study, the incidence was 7.1% and this result is similar to that reported in the study of Poncelet et al [25] In addition, the majority (6/7, 85.7%) of patients with perineural invasion had tumor cells with moderate to poor differentiation. Because of the limited number of cases, further investigations are still required to identify its clinical significance and to understand the actual mechanism of perineural invasion that can lead to poor disease-free and overall survival rates.…”
Section: Discussionsupporting
confidence: 81%
“…We further analyzed the characteristic features of tumor cells among patients who underwent anatomic resection, in order to identify its effect on disease-free and overall survival rates. Previous studies had reported that several pathological factors were related to survival rate; these factors include visceral pleural invasion, [19][20][21][22] vascular invasion, [23] perineural invasion, [24][25][26] histologic grade, [27] and nuclear atypia. [28] Our multivariate analysis indicated that only perineural invasion had a significant effect on disease-free and overall survival rates among N2 NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant associations between skip N2 metastasis and surgical or pathological PL factor or tumor diameter in this study. One mechanism of skip N2 is pleural lymphatic flow [27], and ly and v factors have been reported to predict lymph node metastasis in NSCLC [32]. Therefore, we investigated whether distance to pleura or intersegmental plane, ly factor, or v factor were important predictors of skip N2 metastasis.…”
Section: Discussionmentioning
confidence: 99%